Biological plausibility and stochasticity in scalable VO2 active memristor neurons - Wei Yi (Nature Portfolio, 2018)
The neuromorphic computing based on complementary metal-oxide-semiconductor transistors holds promise for artificial intelligence, but it suffers from the trade-off between scalability and biological fidelity. Yi et al. emulate 23 types of biological neuronal behaviors using scalable VO2 active memristors.